2006
DOI: 10.1007/s00106-005-1346-7
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologie nach Implantation von Lidgewichten

Abstract: Both gold and platinum are suitable for treating lagophthalmos, however, platinum has a higher density and better biocompatibility than gold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
1
8
0
3
Order By: Relevance
“…In contrast, two studies describing chronic inflammatory reactions to gold in humans found a clear predominance of either T cells or B cells. 12,25 An interesting observation in the present study was the tendency of T cells and B cells to occupy separate regions in the lymphocytic infiltrates, resulting in some resemblance to lymphoid follicles. The de novo formation of lymphoid follicles at sites of chronic inflammation has been described 17,27,29,31 and has been reported in lesions associated with inflammation caused by metallic gold in humans.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…In contrast, two studies describing chronic inflammatory reactions to gold in humans found a clear predominance of either T cells or B cells. 12,25 An interesting observation in the present study was the tendency of T cells and B cells to occupy separate regions in the lymphocytic infiltrates, resulting in some resemblance to lymphoid follicles. The de novo formation of lymphoid follicles at sites of chronic inflammation has been described 17,27,29,31 and has been reported in lesions associated with inflammation caused by metallic gold in humans.…”
mentioning
confidence: 58%
“…This is in accordance with studies involving gold and high gold alloys in humans, rats, and dogs in which granulomatous reactions are rarely reported. 1,25,26,30 Conversely, nonprecious metals and alloys of low gold content are reported to cause granulomatous inflammation in guinea pigs and rats. 2,16 T lymphocytes and B lymphocytes were both prominent in the inflammatory infiltrates in the dogs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…По разным данным, частота удаления (включая его замену) имплантата (по причине аллергической ре-акции на золото) составляет от 9,3 до 12%, что не-сколько превышает наши данные (5,7%) [12,15].…”
Section: результатыunclassified
“…Berghaus et al (2003) performed a clinical follow up of 30 platinum chain implants reporting pseudo capsule formation being seen regularly, however, no cases of foreign body reaction or hypersensitivity noted . Schrom et al (2006) reported histopathological evidence of inflammatory infiltration (mixed lymphocytic type) occurring at rates of 12.5% found incidentally following explanation of platinum chain implants following recovery of function or migration …”
mentioning
confidence: 99%